Preserving Local Culture in the Digital Age: Development of History Learning Media Based on Batu Urip Village - Agus Susilo; Sariyatun Sariyatun; Muhammad Akhyar (Journal of Innovation in Educational and Cultural Research, 2026)
The growing threat of globalization to local culture has been met with potential mitigations through improving technology, especially in the field of teaching history. Traditional history-teaching methods disregard the importance of students' local cultural and personal identities, leading to low motivation and limited promotion of students' cultural consciousness. For students' historical literacy and to develop innovative methods of cultural heritage preservation, this paper focuses on developing culture-oriented, technology-enhanced digital history teaching resources grounded in the local culture and folk wisdom of Batu Urip Village. A Research and Development (RD) method and the ADDIE framework were used to engage 60 senior high school students in Lubuklinggau. Participants' historical literacy was assessed using observation, interviews, and questionnaires. Both quantitative and qualitative descriptive techniques were used to analyze the data. The results show that the digital learning resources developed were valid, practical, and effective in significantly enhancing students' cultural-historical understanding, local history, and the value of history. The addition of Batu Urip's culture story to interactive digital media connects contemporary learning with traditional culture. This research developed a culture-oriented digital learning model in response to the Merdeka Curriculum, increasing local cultural literacy and aiding sustainable cultural preservation in the digital era. This research on history teaching was the first of its kind in Indonesia.